Formação das estratégias de marketing no segmento de comercialização de defensivos agrícolas - Centeno, Rodrigo Pozzer (2018)
Agricultural pesticides have the function of protecting agricultural crops through phytosanitary treatments, and thus assist in increasing productivity to feed a constantly growing population. They are inserted in a context where the defense companies, along with resellers and agricultural cooperatives, help in the elaboration of strategies to be created for the sale of these products to the final consumer. In this sense, this study aims to analyze the formation of marketing strategies of organizations, resellers and agricultural cooperatives in the segment of commercialization of agricultural pesticides. It is based on the model of Menon et al. (1999), which analyzes the formation of strategies through the antecedents, processes and results, analyzed through a quantitative research. A structured form with direct interviews was applied in 40 organizations belonging to the Northwest and Southwest mesoregions of Rio Grande do Sul, but because they have subsidiaries besides their headquarters, they cover the strategy used for more than 100 municipalities. The data collection period was carried out from January 9 to April 9, 2018. The results analyzed the dimensions of the isolated model and, in the sequence, the relationship with all the variables by means of the Exploratory Factor Analysis and Cluster Analysis. In the antecedents, the formation of the organizational structure through the managers with or without the aid of the sales force stands out. Branches, besides the organization's headquarters and grain receiving units, also contribute, due to a larger region of operation and differentiated commercial negotiations. In processes, analysis of the strengths and weaknesses of the organization's internal environment and external market threats and opportunities are critical. A well-known brandname company, with award policy, quality products, price, portfolio and relationship, attract the organization. In the results, questions regarding creativity and learning were evaluated through meetings, processes and tools. To evaluate the success of the strategy were considered sales volume, profitability, cost reduction, receipt of accounts, financial growth and new customers. In the control variable, elements such as competition, innovation, industry technology and consumer behavior were considered. Macro-environmental factors also influenced the results of the strategy. In the Exploratory Factor Analysis, we identified seven vectors of common variabilities which explain 73.217% of the total variance of the data. Each of the factors was associated with an analytical dimension of Menon in order to corroborate with the relations indicated in the theoretical model. The Conglomerate Analysis allowed the identification of three types of organizations with specific characteristics in relation to management and marketing. Finally, it is highlighted that the necessary training, for the organizations of the sector to develop marketing strategies, with the purpose of assisting in the commercialization of agricultural pesticides, is the responsibility of a whole group, ranging from organizations, managers and collaborators committed to the objectives, to processes and tools that assist in the search for the creation and implementation of marketing strategies.